Product Quality Control’s Organization and Defects’ Prevention for Electronic Products - V. Myskov, D.; V. Kurenkov, V.; I. Gorobets, A.; A. NazarenkoMirea, M. (International Journal of Engineering and Technology, 2018)
The processes associated with the organization of product quality control and prevention of marriage of electronic products. Stages of control process are revealed, classification of types of control on characteristic signs is carried out.